Collapsin Response Mediator Proteins: Their Biological Functions and Pathophysiology in Neuronal Development and Regeneration - Nakamura, Fumio; Ohshima, Toshio; Goshima, Yoshio (Frontiers in Cellular Neuroscience, 2020)
Collapsin response mediator proteins (CRMPs) are consisted of five homologous cytosolic proteins, all of which are phosphorylated and highly expressed in the developing and adult nervous system. CRMPs are new class of microtubule-associated proteins that play important roles in axon guidance, synapse maturation and cell migration. X-ray structure analysis revealed that central region of CRMPs forms tetramer, and each CRMP monomer consists of N-terminal beta-sheet enriched region and central alpha/beta barrel domain that contains tetramer interfaces. The CRMP C-terminal region may probably stay flexible and random structure and alter its conformation upon posttranslational modification such as phosphorylation, which regulates interaction between CRMPs and various kind proteins including receptors, ion channels, cytoskeletal proteins and motor proteins. Recent studies revealed that CRMPs are involved in various disease states, and thus as target molecules for therapeutic intervention.